Subarachnoid ketamine and ketamine s (+) associated with lidocaine in sheep and goats anesthesia - Dória, Renata Gebara Sampaio; Ferraz, Gesiane Ribeiro Leão; Filippo, Paula Alessandra Di; Lacerenza, Milena Domingues; Fernandes, Letícia Martins; Oleskovicz, Nilson; Valadão, Carlos Augusto Araújo [UNESP] (Elsevier, 2021)
Ten male sheep (Sheep group; SGk) and seven male goats (Goat group; GGks+) were used in this study. The objective was to compare the use of racemic ketamine or ketamine S(+) associated with lidocaine on spinal anesthesia and evaluate if the drugs leads to a surgical anesthesia state, as well as to verify the cardiorespiratory, sedative and motor effects of this technique in these species. After correct placement of the needle in the subarachnoid space, 3.0 mg kg−1 of racemic ketamine (SGk) or ketamine S(+) (GGks+), both diluted in 1.5 mg kg−1 of 2% lidocaine, were administered. Evaluations were performed during orchiectomy, at times 0 (T0), 5 (T5), 10 (T10), 20 (T20), 30 (T30) and 60 (T60) minutes after subarachnoid anesthesia administration. No significant changes in heart and respiratory rates were observed in both experimental groups. All animals showed surgical analgesia and stood conscious or slightly sedated with ataxia immediately after the drugs administration (T5), allowing the execution of bilateral orchiectomy. The ataxia in SGk was classified as severe with recumbency in 80% of the animals, moderate ataxia in 10% of the animals, and mild ataxia in 10% of the animals. All goats (GGks+; 100%) presented severe ataxia and recumbency. At 60 min, animals of both groups were in standing position and with normal gait. Subarachnoid RS-ketamine and ketamine S(+) (3 mg kg−1), associated with lidocaine in sheep and goats, produces surgical anesthesia and recumbency without causing cardiorespiratory abnormalities, regurgitation and bloating.
Keywords: Analgesia; Anesthesia; Ruminants; Sedative